PECULIARITIES OF ORAL INTERPRETATION (Spectrum Journal of Innovation, Reforms and Development, 2023)
This paper is intended to discuss what deontological principles mean for interpretors and reveal their role in consecutive and simultaneous translation. Besides, it there will be explained an etiquette and consiciness in translation.